British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages APRIL 30, 1938 GENERAL MEDICAL SERVICE FOR THE NATION SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL 265 employers and workers but with the general practitioners throughout the areas concerned. 105. In view of the important new developments in industrial technique and management the Association welcomes the widening of the conception of industrial medicine to include all factors in industry which can directly or indirectly affect the health and well-being of the worker. 106. Fracture and Rehabilitation Services. — Following an exhaustive inquiry by a special committee, the Association has reached the conclusion that for the proper and efficient treatment of fractures and other associated injuries of the limbs an organized fracture service is necessary. The essential conditions of such an organized fracture service are segregation of cases, continuity of treatment, unity of control, and after-care. 107. It is believed that segregation of cases into one department where they can be uniformly handled by a specially trained and experienced staff is highly desirable. Co-ordination of the successive stages of treatment is essential, and the staff of a fracture unit should be responsible for the treatment of the patient from beginning to end, from the primary reduction to a complete restoration of function. Segregation and continuity achieve their greatest value only if there is unity of control. All the stages of treatment of each case need not only expert supervision but supervision by one expert. 108. The phase of after-care is the one most commonly neglected to-day. Excellent primary treatment is of little value in many fractures unless it is followed by a phase of active exercise directed to a complete restoration of function. The word "rehabilitation" is applicable to the stage between the completion of a course of massage and exercises in a massage department and the point when the stresses and strains of heavy work can be undertaken. Because of the difficulty of securing light work the Association urges the establishment of rehabilitation centres where physical and mental redevelopment can be achieved by games, by activities in the gymnasium and the swimming pool, and by graduated work. V. ADMINISTRATION 109. The scheme as outlined in these proposals raises questions as to the machinery of government. Until the passage of the National Health Insurance Act in 1911, the central Government had not exercised any executive functions in relation to health except those of the Home Office in connexion with the administration of the Factories Acts. The Poor Law Board set up in 1834 and its successors, the Local Government Board and the Ministry of Health, have continued to control in some detail the administration of the Poor Law, including the medical services it provides. Similar powers have been exercised in Scotland by the Scottish Board of Health and the Department of Health for Scotland. Even under the Poor Law, however, and more especially in connexion with the Public Health and allied Acts, the expanding medical and public health services have been initiated and managed through some kind of local authority. The Insurance Act was a break-away from the policy underlying most of the developments in the association between government and the health of the people. No doubt because of the method by which the insurance scheme was financed, and because of the part which friendly societies, trade unions, and insurance corporations were destined to take in it, the scheme was placed on a national basis, only certain details relating to the medical and pharmaceutical services being delegated to new local bodies, the insurance committees. 110. The Association believes that there is great advantage in the uniformity of practice and of conditions of service which the national health insurance system ensures. The foregoing proposals assume that a satisfactory general medical service can be built up on the basis of the extension to dependants of the type of provision the national health insurance system makes, and by the enlargement of the content of statutory medical benefit. The Association maintains, in particular, that the same determination of policy should apply to the special provision of maternity services. 111. It is realized, however, that the administration of services for the health and welfare of the people through local elected bodies is an established feature of the machinery of government in this country. In so far as voluntary effort is inadequate, hospital provision and the care of the sick poor are likely to continue to be a responsibility of local authorities. The especial need of the tuberculous, of those suffering from infectious diseases (including venereal diseases), the welfare of women and children, and the peculiar problems of mental disease and deficiency require organization and co-ordination with a general domiciliary service. Organization and co-ordination are likely to remain local, and the Association appreciates the advantages in elasticity and the preservation of local public interest which the system bears, so long as variations in methods and in the quality and conditions of service are not too extreme, and service is not too rigidly limited by geographical boundaries. 112. The effect of the Local Government Acts of 1929 and 1933, and the Public Health Act, 1936, has been to enlarge the field of public health responsibility of the larger units of administration in England and Wales — namely, the counties and county boroughs. The intention is to reduce the number of smaller units (the county districts), to increase their efficiency on the medical side, and to rationalize the personal services they render to the public, objects which have so far been very imperfectly attained. It is still the case that, while the larger and more costly medical and allied services are the province of the counties and county boroughs, almost the whole of the responsibility for sanitation, for housing, and for the prevention of the spread of infectious disease remains with county districts (however small), and many of the moderately large county districts retain the administration of schemes relating to maternity and child welfare and the health of elementary school children, services which impinge upon similar functions of the county councils and other related functions of the latter authorities, such as general hospital provision and the supply of midwives. In Scotland unification of medical and public health services has gone much further in counties than in England and Wales, but many of the so-called "large burghs" (with population 20,000 or more) retain a large measure of autonomy in public health affairs. While the century-old divergence of Poor Law medical and public health administration has been overcome, the medical and pharmaceutical service for insured persons is administered through a separate local body, the insurance committee, in each county or county borough (large burgh in Scotland). In all areas the only statutory link between voluntary hospitals and local authorities is provided by the duty imposed only upon the latter to consult the former in connexion with any proposed extension of their hospital provision. (In Scotland, under similar circumstances, the Department of Health must consider the existing voluntary hospital provision in relation to any scheme submitted by a local authority for reorganizing hospital facilities in its area.) 113. The Association considers that the scheme it has outlined calls not only for the maximum possible degree of co-ordination but also for unification of administration, centrally and locally. Except for the failure to give complete effect to the objects of the Ministry of Health Act, 1919, in relation to the control of the school health service, this has been largely attained at the centre, since the Ministry is responsible for public health, insurance, and poor relief; and the Board of Control and the Central Midwives Board are answerable to the Minister. The Department of Health for Scotland and the Secretary of State for Scotland are analogously situated. To attain 292/847/1/60